Current perspectivesin pathogenesis and antimicrobial resistance of enteroaggregative Escherichia coli. (August 2015) - Kong, Haishen; Hong, Xiaoping; Li, Xuefen
Abstract: Enteroaggregative Escherichia coli (EAEC) is an emerging pathogen that causes acute and persistent diarrhea in children and adults. While the pathogenic mechanisms of EAEC intestinal colonization have been uncovered (including bacterial adhesion, enterotoxin and cytotoxin secretion, and stimulation of mucosal inflammation), those of severe extraintestinal infections remain largely unknown. The recent emergence of multidrug resistant EAEC represents an alarming public health threat and clinical challenge, and research on the molecular mechanisms of resistance is urgently needed. Highlights: EAEC causes acute and persistent diarrhea and extraintestinal infections. The recent emergence of multidrug resistant EAEC represents an alarming public health threat and clinical challenge. Enhancing worldwide surveillance of EAEC infections will support studies of the pathogenic and resistance mechanisms and development of prevention and treatment programs.